The Analysis of Students’ Learning Outcomes Majoring in Natural Science and Social Science at Accounting Education Study Program - Sahade, Sahade; Ngampo, M. Yusuf A. (Dinamika Pendidikan, 2016)
This research aims to determine the differences of students’ learning outcomes majoring in natural and social sciences at Accounting Education Department in the Faculty of Economics, Makassar State University. Population of research was students of Accounting Education Department in the year of 2011 to 2012. Samples were 50 undergraduate students who graduated from natural science and 50 undergraduate students who graduated from social science. It used purposive sampling with the certain criteria. Data were collected by using questionnaires and data on students’ study backgrounds was taken from simpadu. Then, data were analyzed by descriptive statistical analysis. Findings show that the averages of students’ learning outcomes on both Introduction to Accounting 1 and Introduction to Accounting 2 Subjects were 2.89 for students who graduated from natural science and 2.81 for students who graduated from social science. Then; students’ learning outcomes who graduated from natural science on Introduction to Accounting 1 subject was 2.80 and 2.98 for Introduction to Accounting 2. Whereas; students’ learning outcomes who graduated from social science for Introduction to Accounting 1 was 2.95 and Introduction to Accounting 2 was only 2.68. It can be concluded that students’ learning outcomes on Introduction to Accounting 1 and Introduction to Accounting 2 who graduated from Social science got the lower scores than students who graduated from natural science. It happened because the learning method which used by Natural science graduates more practical and the Social science graduates usually had discussions because they thought they already had the basic knowledge of accounting.